Development and application of ELISA assays for the detection of two members of the family Luteoviridae infecting legumes: Pea enation mosaic virus (genus Enamovirus) and Bean leafroll virus (genus Luteovirus). (16th April 2014) - Vemulapati, B.; Druffel, K.L.; Husebye, D.; Eigenbrode, S.D.; Pappu, H.R.
Abstract An antigen‐coated plate enzyme‐linked immunosorbent assay (ACP‐ELISA) method was developed and validated for the detection of Bean leafroll virus (BLRV) and Pea enation mosaic virus (PEMV), two of the important viral pathogens of several legume crops. The coat protein (CP) gene of each of the viruses was bacterially expressed as a fusion protein containing an N‐terminal hexa‐histidine tag and used as an antigen to produce antisera in rabbits. The antiserum to BLRV could detect the virus in leaf samples in up to 1:1000 dilution, and the PEMV antiserum detected the homologous virus in leaf samples of dilutions up to 1:6400. No serological cross‐reactivity was observed between anti‐BLRV and anti‐PEMV sera. The ACP‐ELISA assays were then used for estimating the prevalence of these two viruses in alfalfa, pea and vetch over a three‐state area in the US Pacific Northwest over a 2‐year period and virus incidence was mapped. Availability of rapid and sensitive ELISA assays facilitate virus disease mapping efforts and screening germplasm for virus resistance.